MULTIMEDIA INTERAKTIF “KOPAJA” PENINGKATAN HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN TATA BUSANA PROGRAM PAKET C - Suwarnoto - Suwarnoto (STKIP PGRI TULUNGAGUNG, 2022)
The author developed a concept of learning interactive multimedia fashion by utilizing Information Technology (IT). The learning process by utilizing technology will make learning methods more passionate for students, so that students continue to be motivated to learn the subject of Dress Design. All learning components by the author are then arranged in a framework of Interactive Multimedia learning strategies